The relationship between foot posture, body mass, age and ankle, lower-limb and whole-body flexibility in healthy children aged 7 to 15 years - Hawke, Fiona (J Foot Ankle Res, 2016)
BACKGROUND: The complex relationship between foot posture, flexibility, body mass and age in children is not well understood. The objectives of this post hoc analysis were to explore the relationships between foot posture, flexibility, body mass in children aged seven to 15 years. METHODS: Thirty healthy, asymptomatic children (20 girls, 10 boys) aged 7 to 15 years with a mean age (SD) of 10.7 (2.3) years, were recruited through the Auckland University of Technology (AUT) Podiatry Clinic, Auckland, New Zealand. Clinical data were collected by a podiatrist with 20 years’ experience and included: height and weight (for Body Mass Index), Foot Posture Index-6 (FPI), Beighton score, Lower Limb Assessment Scale score (LLAS); and ankle lunge angle. For this post hoc analysis, Pearson’s test and Spearman’s rho were used to explore relationships between variables. Statistical significance level was p < 0.05. RESULTS: Data for each of the 30 participants for each variable were included in analyses, which returned the following statistically significant results: higher FPI was associated moderately with higher Beighton score (r = 0.44, p = 0.01); greater lunge angle was associated moderately with higher Beighton (r = 0.40, p = 0.02) and LLAS (r = 0.42, p = 0.02) scores; older age was associated strongly with higher BMI (r = 0.52, p = <0.01) and moderately with lower Beighton (r = −0.41, p = 0.024) and LLAS (r = −0.40, p = 0.03) scores; and higher Beighton score was associated strongly with higher LLAS (r = 0.85, p = <0.01). There was no difference in foot posture between girls and boys (p = 0.21). CONCLUSIONS: In this sample of healthy, asymptomatic children age 7 to 15 years, children with a more pronated foot type exhibited greater lower limb and whole-body flexibility, but not greater ankle joint flexibility. There was strong agreement between lower-limb and whole-body flexibility. This study highlights the importance of assessing the paediatric flat foot in the context of a developing body.